2010
DOI: 10.1016/j.burns.2009.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Sclerosis therapy of bronchial artery attenuates acute lung injury induced by burn and smoke inhalation injury in ovine model

Abstract: Introduction-In thermally injured sheep, there is more than a 10-fold increase in bronchial blood flow following smoke inhalation. It was previously reported that sclerosis of the bronchial artery prior to smoke exposure would reduce the pathophysiology of the inhalation insult. We hypothesized that sclerosis of the bronchial artery after insult would attenuate smoke/burn-induced acute lung injury.Methods-Through an incision at the 4th intercostal space, a catheter was placed via the esophageal artery into the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Building on these initial findings, the same group then exposed the sheep to the burn/smoke inhalation injury first, then used a catheter to inject 70% ethanol into the bronchial artery one hour after injury and compared it to groups with saline injection and with no injury. Again, the injured groups showed markedly worse blood gas analyses and pulmonary mechanics, but those undergoing bronchial artery sclerosis with ethanol had decreased bronchial blood flow and less severe changes in their blood gases and pulmonary mechanics [105]. …”
Section: Medical Adjuncts For Treatment Of Smoke Inhalationmentioning
confidence: 99%
“…Building on these initial findings, the same group then exposed the sheep to the burn/smoke inhalation injury first, then used a catheter to inject 70% ethanol into the bronchial artery one hour after injury and compared it to groups with saline injection and with no injury. Again, the injured groups showed markedly worse blood gas analyses and pulmonary mechanics, but those undergoing bronchial artery sclerosis with ethanol had decreased bronchial blood flow and less severe changes in their blood gases and pulmonary mechanics [105]. …”
Section: Medical Adjuncts For Treatment Of Smoke Inhalationmentioning
confidence: 99%
“…In a smoke inhalation ovine model, bronchial artery flow (normally 1% of cardiac output) was increased 15-fold in the left main bronchus, 20-fold in the right main bronchus, and approximately 4-and 6-fold in the right and left lungs, respectively (2). Sclerosis of the bronchial artery after smoke inhalation has been reported to greatly improve lung function and to drastically reduce animal mortality (2,4). Thus, bronchial artery sclerosis resulted in a statistically significant improvement of the arterial partial pressure of oxygen/fraction of inspired oxygen ratio and led to attenuation of the increase of pulmonary pressure and elevation of pulmonary artery vascular resistance, suppression of formation of bronchial casts; and reduction of myeloperoxidase activity compared with an animal smoke inhalation control group (4).…”
Section: Editormentioning
confidence: 99%
“…Cellular and humoral mediators of inflammation produced in response to local pulmonary injury may enter into the bronchial circulation and could be delivered to the whole pulmonary parenchyma, as the bronchial arterial circulation mainly drains into the pulmonary arterial circulation by precapillary anastomoses. Thus, the increase in bronchial circulation could spread inflammatory mediators and cells throughout the whole pulmonary parenchyma and accelerate lung damage (2,4). In 2012, Hamahata et al (4) concluded that with the advances in interventional radiology, it would be possible to suppress the bronchial artery flow in situations of pulmonary hyperemia in humans.…”
Section: Editormentioning
confidence: 99%